Internship students practice in library services at Dinas Arsip dan Perpustakaan (Disarpus) of Bandung City - Nisrina Sifahumaria (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Program Penguatan Profesional Kepustakawanan Non Kependidikan (P3KNK) at the Dinas Arsip dan Perpustakaan (Disarpus) of Bandung City is a practical training program that provides students with direct experience in library management and services. The program was implemented over 40 working days and included shelving, circulation services, children’s and youth services, user assistance, information searching, weeding, and restoration of library materials. Students also applied Information and Communication Technology (ICT) using computers, spreadsheets, web browsers, email, and INLIS Lite. The program was carried out in three phases: pre-implementation, implementation, and post-implementation. The results indicate that the P3KNK program supports library services by assisting librarians with routine operational activities and improving service delivery, particularly in collection organization and user services. However, several challenges were identified, including limited human resources, the absence of written guidelines for preservation activities, constraints in information retrieval, user misunderstandings regarding loan extensions, and limited internship duration. These challenges were addressed through coordination with librarians and collaboration among student participants. Overall, the implementation of the P3KNK program contributed to student professional development while simultaneously supporting the continuity of library services at Disarpus Bandung City.   Abstrak Program Penguatan Profesional Kepustakawanan Non Kependidikan (P3KNK) di Dinas Arsip dan Perpustakaan (Disarpus) Kota Bandung merupakan program praktikum yang memberikan pengalaman langsung kepada mahasiswa dalam pengelolaan dan layanan perpustakaan. Program ini dilaksanakan selama 40 hari kerja dengan berbagai kegiatan, seperti penjajaran koleksi (shelving), layanan sirkulasi, layanan anak dan remaja, pendampingan pemustaka, penelusuran informasi, weeding, serta restorasi bahan perpustakaan. Mahasiswa juga menerapkan Teknologi Informasi dan Komunikasi (TIK) melalui penggunaan komputer, spreadsheet, web browser, email, dan INLISLite. Pelaksanaan program meliputi tiga tahap, yaitu pra pelaksanaan, pelaksanaan, dan pasca pelaksanaan. Hasil kegiatan menunjukkan bahwa program P3KNK mendukung layanan perpustakaan melalui bantuan tenaga dalam pelaksanaan tugas operasional rutin dan kelancaran alur layanan, khususnya pada penataan koleksi dan layanan pemustaka. Namun, terdapat beberapa kendala, seperti keterbatasan sumber daya manusia, ketiadaan panduan tertulis dalam kegiatan preservasi, permasalahan temu balik informasi, kesalahpahaman pemustaka mengenai perpanjangan peminjaman, serta keterbatasan waktu magang. Kendala tersebut diatasi melalui koordinasi dengan pustakawan dan kerja sama antar praktikan. Secara keseluruhan, pelaksanaan program P3KNK berkontribusi pada pengembangan kompetensi profesional mahasiswa sekaligus mendukung keberlangsungan layanan perpustakaan di Disarpus Kota Bandung. Kata Kunci: Disarpus Kota Bandung; layanan perpustakaan; praktikum kepustakawanan